Respuesta :

Answer:

2

Step-by-step explanation:

3(6-4)/3

3(2)/3

6/3 = 2

Answer:

Option: C) 2

Step-by-step explanation:

Given question,

  • To find the value of expression

Expression:

  • [tex] \frac{3(a - 4)}{b} [/tex]

Given values:

  • a = 6 and b = 3

Solution:

[tex] = \frac{3(a - 4)}{b} [/tex]

  • (Substituting values of a = 6 and b = 3)

[tex] = \frac{3(6 - 4)}{3} [/tex]

  • (On Simplification)

[tex] = \frac{3 \times 2}{3} [/tex]

  • (On further Simplification)

[tex] = \frac{6}{3} [/tex]

  • (On dividing 6 by 3)

= 2 (Ans)

ACCESS MORE